120 Mild cognitive impairment? Forget about it!. (8th June 2022) - Bencivenga, Patricia
Abstract : Industry-sponsored 'disease awareness campaigns' can be expected to lead to an epidemic of diagnoses of both Alzheimer's Disease (AD) and Mild Cognitive Impairment (MCI). Age-related cognitive changes are normal, and the incidence of dementia in Europe and North America has declined in recent decades. Nonetheless, 2 in 5 adults aged 50–64 worry about developing dementia. Although AD is a heterogenous group of syndromes difficult to diagnose, manufacturers of treatments for AD are attempting to solidify diagnoses based on imaging studies alone – even in individuals with normal cognition. In addition, mild cognitive impairment (MCI) is being cast as a precursor to AD. However, diagnosing MCI is problematic because the diagnosis has been plagued with ambiguity. Estimates of the prevalence of MCI vary widely, and MCI does not invariably lead to AD; it may reverse or remain stable over time. Additionally, cognitive changes may be caused by depression, polypharmacy, hearing or visual loss, nutritional deficiencies, and many other factors. Some memory problems and changes are part of normal aging. Reifying MCI as an early stage of AD will cause forgetful, but otherwise healthy, people to seek diagnosis and treatment. Some efforts to drive forgetful people to seek medical treatment are funded by manufacturers of drugs to treat Alzheimer's and MCI. For example, unbranded marketing efforts by Biogen to position and market Aduhelm (aducanumab), an anti-amyloid therapy of questionable efficacy and proven risks, include: ItsTimeWeKnow. com, a website that attempts to educate consumers about the symptoms of MCI due to AD that offers a symptom quiz for consumers. IdentifyAlz.com, a website targeted to healthcare professionals to educate them on the signs and symptoms of MCI due to AD. MyBrainGuide.org, another website attempting to educate consumers about MCI and AD that offers a memory questionnaire funded by Biogen that was on UsAgainstAlzheimer's website, a non-profit patient advocacy organization funded by pharmaceutical companies. No matter how anyone answers the BrainGuide or ItsTimeWeKnow quizzes, a doctor visit is always recommended. The purpose of these 'educational' sites and other promotions appear to be to increase diagnoses of 'MCI due to Alzheimer's Disease'. While aducanumab is currently the only FDA-approved treatment that treats MCI due to Alzheimer's Disease, other drugs are in the pipeline. Overdiagnosis of MCI and AD will have a profound adverse effect on public health.